Milimeter wave carrier generation using stimulated brillouin scattering in optical fiber - Muzni, Aishah (2010)
Radio Over fiber (RoF) applies the concept when radio signals are transmitted over optical fiber from central station (CS) to several remote base stations (BS). These such system are applied in a number of applications such as in Distributed Antenna System (DAS) to increase the coverage area of RF services in the building for mobile communications and broadband services. For wireless communication links, gigabit per second data transmission is required to keep up with the remarkable speed up. Delivering high speed data require using high carrier frequency up to 60GHz. The way to increase the bandwidth of wireless link is by the exploitation of milimeter waves (mm-waves). Several techniques have been proposed for the optical generation of mmwaves such as direct-modulation, external modulation and optical heterodyning. This project will focus in proposing and investigating an alternative method to generate milimeter wave in RoF. The proposed method is based on the non linear effect of Stimulated Brillouin scattering (SBS) in optical fiber. The SBS effect will be utilized for the optical generation and amplification of milimeter waves. The system is designed in such a manner to measure Brillouin stokes and the reflected input power launched into the optical fiber once the Brillouin threshold is reached. A loopback concept is used to allow propagation of the light in the opposite direction causing the stokes wave in SBS interaction comes from both external optical signal and higher signal internally generated as a result of spontaneous Brillouin scattering. The analysis will present the proposed design using SBS technique, system model and simulation result for the generation of RF carrier. The design successfully managed to generate RF carrier of 10GHz to 60GHz.